Effect Effect of Foot Massage Therapy on Patient’s Non-Invasive Hemodynamic Status in The Intensive Care Unit - Wisma Dewi Ni Putu; Ni Komang Sukraandini; I Nyoman Dharma Wiasa; Putu Sudarmika (Nursing and Health Sciences Journal (NHSJ), 2023)
Intensive care is a care service for critical, acute, and life-threatening patients with hemodynamic instability. The use of a ventilator can make discomfort to the patients and then affect the patient's hemodynamics. Foot massage can be applied to intensive patients. This study aims to determine the effect of foot massage on non-invasive hemodynamic status patients in the ICU of the Sanglah General Public Hospital. The quasi-experimental design with a time series approach used, involve 12 patients using a purposive sampling technique. A foot massage was carried out for 30 minutes and hemodynamic measurements were taken 30 minutes later. The research data were analyzed using the Friedman test then continued with the post-hoc Wilcoxon Sign Rank test analysis. Foot massage therapy was given a significant effect on non-invasive hemodynamic status in patients in ICU, including decreasing respiratory frequency (p=0.002), decreasing MAP (p=0.002), decreasing heart rate (p=0.002), and increasing oxygen saturation (p=0.002). It provides a relaxation response that stimulates the sympathetic nervous system to decrease its activity and increase the work of the parasympathetic nerves which influence decreasing heart rate and blood pressure so that there is a balance between oxygen and carbon dioxide in the tissues then reduce the respiratory rate to become normal.